Ācārya Ānandaśaṅkara Dhruva smāraka grantha : Gujarātī-Hindī vibhāga - Dhruva, Ānandaśaṅkara Bāpubhāī, 1859-1942; Parikh, Rasiklal Chhotalal, 1897-; Trivedī, Ratilāla Mohanalāla, 1894-; Jośī, Umāśaṅkara, 1911- (SAMP early 20th-century Indian books project, 1944)
Festschrift in honor of Ānandaśaṅkara Bāpubhāī Dhruva, 1859-1942, Gujarati author; chiefly on Gujarati literature.